The relationship between trust in teacher and motivation to learn of the street children in Banda Aceh, Indonesia - Cut Dhiya Amalina; Marty Mawarpury; Risana Rachmatan (Proceedings of AICS - Social Sciences, 2013)
Street children tend to ignore educational demand as a result of economical and environmental factor. The absence of parent role put the teacher as a reliable substitute in motivating the children to learn. This study was led to investigate the relationship between trust in teacher and learning motivation of street children. The study used quantitative method by purposive sampling involving 44 street children from third grade of elementary school to third grade of upper secondary school. UPTD (Regional Technical Implementer Unit) Rumoh Seujahtera Aneuk Nanggroe under Dinas Sosial Provinsi Aceh (Social Department of Aceh) auspice. Data collecting method used Trust Scale with reliability of 0,832 and Learning Motivation Scale with reliability of 0,780. Analysis method used Pearson correlation technique which resulted in correlation coefficient r=0,319 and  p0,035 (p0,05). The result revealed significant positive relationship between trust in teacher and learning motivation of street children. Higher trust in teacher would be followed by better learning motivation of street children.Keywords: Trust, learning motivation, street children